Mortality Prediction in ICU Patients on Mechanical Ventilation at RSUD Pasar Minggu - Sitti Umniyatul Azkiyah; Lili Indriawati; Anna Sunita (CV. Inara, 2026)
Although effective in saving lives, mechanical ventilation also carries the risks of serious complications. This study aimed to identify predictor factors for mortality in patients on mechanical ventilators in the ICU. Methods: This retrospective cohort study analyzed medical records from 424 patients, were obtained through simple random sampling from 614 patients meeting the inclusion and exclusion criteria. Data analysis was conducted using IBM SPSS Statistics version 22. Bivariate analysis was conducted using the chi-square test to identify associations between independent variables and mortality, followed by multivariate analysis using logistic regression to determine significant predictors of mortality. Result : The mortality rate was 51%. Multivariate analysis identified nine mortality factors. ICU admission from inpatient ward (RR=2.688), GCS (RR=2.674), respiratory failure (RR=18.187), ROSC (RR=6.754), septic shock (RR=3.885), renal failure (RR=2.024), and reintubation (RR=2.257) were found to increase the risk of mortality, while length of ICU stay (RR=0.323) and length of ventilator use (RR=0.313) were identified as protective factor. On the other hand, variables such as age, gender, pneumonia, stroke, and tracheostomy did not have a real influence on mortality in this study.Conclusion: ICU admission from inpatient ward, GCS, respiratory failure, ROSC, septic shock, renal failure, and reintubation were found to be predictors of mortality in patients with mechanical ventilator in ICU.